Detecting the probability of diabetic retinopathy / Nurul Farhanah Khairol Nizar - Khairol Nizar, Nurul Farhanah (2020)
Diabetic Retinopathy (DR) has become a common disease that caused blindness or vision impairment especially to diabetic patients. The problem of Diabetic Retinopathy patients only able to detect the disease by having a check-up which eye screening may cost a price at a certain high range which it has been estimates the lowest is at RM1,984. The purpose of this project is to develop a system to help in detecting the possibility of having Diabetic Retinopathy using rule-based system on web-based application. The researcher apply rule bases from fuzzy logic algorithm to determine the possibility outcomes of the disease by using 4-phased design and development research which consists of planning phase, design phase, development phase and documentation phase. In the conclusion, the development of rule-based system should help patients to find the probability in getting the eye disease.